Kerjaya Wanita Di Peringkat Pengurusan Tertinggi Negara Menurut Perspektif Al-Qur'An Dan Hadis - Ismail, N. T.; Che Pa, B.; Abdul Rahman, M. Z. (Universiti Sains Islam Malaysia, 2024)
The involvement of women in top management of the country is an effort being intensified by the government in achieving the 30 per cent target of women at decision-making levels in the public sector. Career in top management of the country is a leadership field that needs to be seen more clearly when it comes to women. Hence, this study attempts to understand the perspectives of the Qur'an and the hadith in view of Islamic law on this issue as well as taking the views of Islamic scholars. This study uses the most authoritative proofs of Qur'an and hadith in ensuring the resolution of the argument presented. The findings show that Islam permits the involvement of women at the state's highest level of leadership except the caliph's position.